Study of Chinese Adolescents with Mental Health Problems from the perspective of social inclusion - Tu, Yifang (Transactions on Social Science, Education and Humanities Research, 2024)
Chinese adolescent’s mental health problems are a social concern. Based on the theory of social inclusion and China's cultural background and national conditions, this paper expounds the dilemma faced by Chinese adolescents with mental problems and puts forward solutions from the perspectives of national policies, institutional settings, and schools.